Facilitative Village Leadership in Collaborative Village-Owned Enterprise Development - Ival Faris Setiawan; Hari Karyadi; Suji (Journal of Transformative Governance and Social Justice, 2026)
These case studies explore how facilitative leadership helps build collaboration in “Dana Asri Sejahtera,” a Village-Owned Enterprise in Wonoasri Village, Jember Regency, using information from people who were selected for specific reasons—including the village head, the business manager, local community members, local partners, and an expert in the field of local and regional economy—which was put together by interviews, observations, and analysis of documents, and reviewed using the Miles, Huberman, and Saldaña model, with triangulation to check the information. The research findings reveal five related leadership mechanisms—dialogue, building trust, consultation, understanding, and conflict mediation—in the village head’s efforts to build a collaborative network by connecting public authority, and academic knowledge into a collaborative network, making it easy to scale up services like small loans, market stalls, and payments, which in the end leads to more participation and higher village income. How well this works, though, has a lot to do with internal factors like human skills, communication, and trust, as well as external factors like policy support, partnerships, academic networks, and economic opportunities. We conceptualize the facilitative leadership of villages as a type of collaboration infrastructure that transforms the participation of multiple actors into the capacity for action, based on the idea that in order to make things work, we need to build systems for evaluation, partnerships, and the distribution of leadership that go outside of individual leaders.